ASSA14-03-21 Polymorphisms of PON1 gene are associated with coronary artery disease. (1st December 2014) - Liu, T; Zhang, X; Zhang, Y; Liang, Z; Cai, W; Sun, Y; Yan, C; Han, Y
Abstract : Background: Paraoxonase 1 (PON1) is a plasma enzyme that is capable of inhibiting the progression of atherosclerosis, and is significantly associated with the susceptibility of coronary artery disease (CAD). Recently, PON total protein expression was found in human aortic tissue and it played an important role in progression of atherosclerosis. For studying its crucial role in preventing CAD, we performed the PON1 immunohistochemical analysis in human coronary arteries, explored its polymorphisms and plasma status, and analysed its association with the risk of CAD. Methods: The expression of PON1 in human coronary arterial tissues was detected by immunohistochemical staining analysis. PON1 gene polymorphisms were determined by polymerase chain reaction (PCR) direct sequencing in 2456 unrelated Chinese Han individuals. Serum PON1 level was reflected indirectly by PON1 activity towards paraoxon and phenylacetate by spectrophotometry separately and directly by its concentration using human enzyme linked immunosorbent kit (ELISA). Results: Immunohistochemical analysis showed that PON1 expression in human coronary arteries was lower in atherosclerotic arteries than in normal arteries. Among all of the studied polymorphisms, only PON1 Q192R (rs662) had a significant effect on the risk of CAD (p = 0.001). In a logistic regression model, after adjusting the conventional risk factors of CAD, R allele carriers had a significantly higher risk of CAD than other allele carriers. Both serum PON1 activity and concentration were significantly reduced in CAD patients compared with the controls (p < 0.05), and highly associated with Q192R polymorphisms. Conclusion: Decreased PON1 expression in human atherosclerotic coronary arteries was associated with CAD. Moreover, our finding indicated that PON1 Q192R polymorphism might be a genetic risk factor for the susceptibility of CAD in Chinese Han population, and the R allele might be an independent predictor for CAD.